PENGARUH ANNEALING DENGAN TEMPERATUR 1050ºC TERHADAP SIFAT MEKANIK STEEL 316 HEAT NUMBER NY211130AV12 - Aulia Fajrin; Freddy Pranata; Domi Kamsyah; Adhitomo Wirawan; Nadhrah Wivanius (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2024)
Heat treatment aims to obtain certain properties by a combination process between heating and cooling processes of the metal or its alloy in a solid state. It is important to know the physical and mechanical properties of metals. By knowing the physical and mechanical properties of the metal without compromising its properties and conditions, the metal can be used as needed. If there is a head crack when the wire is further processed into screws, it is necessary to analyze the hardness and strength of the stainless steel wire. Annealing is done to soften the wire. Annealing aims to increase ductility and reduce internal stresses. This study aims to determine the effect of annealing at a temperature of 1050ºC on the hardness and strength of stainless steel wire 316 heat number NY211130AV12. The experimental method was used in this study. The results of the analysis are based on test specimens with numerical data. From the research data shows that there is a decrease in wire hardness, strength and tension in the wire after annealing. Meanwhile, the ductility of the wire increases after annealing.